DESIGN AND DEVELOP AUTOMATION SYSTEM FOR SAVING ELECTRICAL ENERGY IN THE STTAL OFFICE ROOM - Sutrisno Sutrisno; wawan kusdiana; Amri Rahmatullah; Bagiyo Herwono (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
The use of electricity in offices has been considered too wasteful. This is caused by human negligence in controlling their use. For this reason, this research was carried out as an effort to find the right method to reduce the high electricity consumption in offices. This research was conducted in the STTAL classroom, Bumimoro, Surabaya. From the results of the calculation, the total heat load in the classroom is 32,048.3 BTU or ± 4 PK. Total installed AC capacity is only 2 PK. This automation tool is a system that works automatically to regulate the use of electrical equipment based on parameters that have been determined in a program such as the presence or absence of humans, the level of light intensity and room temperature. Data collection is carried out for 6 days in the classroom, 3 days without tools and 3 days using the automation tool. Furthermore, the data is compared to the graph and the savings are calculated. The result, on day 1 is 56.11%, days 2 and 3 are 10.26% and the average savings for the 6-day trial is 33.43%. All data is recorded automatically on a micro sdcard and information about the amount of electricity consumption and the ON / OFF feature of electrical equipment can also be accessed via a smartphone with a wifi network so that users will find it easier to monitor the use of electrical equipment in the classroom.Keywords: electricity waste, heat load, automation system, electricity monitoring, electricity savings.